Disrupted expression of mitochondrial NCLX sensitizes neuroglial networks to excitotoxic stimuli and renders synaptic activity toxic - Hertle, Anna M.; Yan, Jing; Bas Orth, Carlos; Tan, Yan-Wei; Sekler, Israel; Bading, Hilmar (The journal of biological chemistry, 2022)
The mitochondrial solute carrier family 8 sodium/calcium/lithium exchanger, member B1 (NCLX) is an important mediator of calcium extrusion from mitochondria. In this study, we tested the hypothesis that physiological expression levels of NCLX are essential for maintaining neuronal resilience in the face of excitotoxic challenge. Using an shRNA-mediated approach, we showed that reduced NCLX expression exacerbates neuronal mitochondrial calcium dysregulation, mitochondrial membrane potential (ΔΨm) breakdown, and reactive oxygen species generation during excitotoxic stimulation of primary hippocampal cultures. Moreover, NCLX knockdown—which affected both neurons and glia—resulted not only in enhanced neurodegeneration following an excitotoxic insult but also in neuronal and astrocytic cell death under basal conditions. Our data also revealed that synaptic activity, which promotes neuroprotective signaling, can become lethal upon NCLX depletion; expression of NCLX-targeted shRNA impaired the clearance of mitochondrial calcium following action potential bursts, and was associated both with ΔΨm breakdown and substantial neurodegeneration in hippocampal cultures undergoing synaptic activity. Finally, we showed that NCLX knockdown within the hippocampal cornu ammonis 1 region in vivo causes substantial neurodegeneration and astrodegeneration. In summary, we demonstrated that dysregulated NCLX expression not only sensitizes neuroglial networks to excitotoxic stimuli but also notably renders otherwise neuroprotective synaptic activity toxic. These findings may explain the emergence of neurodegeneration and astrodegeneration in patients with disorders characterized by disrupted NCLX expression or function, and suggest that treatments aimed at enhancing or restoring NCLX function may prevent central nervous system damage in these disease states.